2020
DOI: 10.1016/j.dnarep.2019.102741
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of DNA adducts by edited and unedited forms of DNA glycosylase NEIL1

Abstract: Pre-mRNA encoding human NEIL1 undergoes editing by adenosine deaminase ADAR1 that converts a single adenosine to inosine, and this conversion results in an amino acid change of lysine 242 to arginine. Previous investigations of the catalytic efficiencies of the two forms of the enzyme revealed differential release of thymine glycol (ThyGly) from synthetic oligodeoxynucleotides, with the unedited form, NEIL1 K242 being ≈30-fold more efficient than the edited NEIL1 K242R. In contrast, when these enzymes were rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 75 publications
2
35
0
Order By: Relevance
“…Known classical NHEJ players include Ku70 (XRCC6), Ku80 (XRCC5), XRCC4, DNA ligase IV, and DNA-PKcs (29), whereas the nonclassical (or alternative) NHEJ pathway uses XRCC1 and DNA ligase III for DNA end joining (30,31). Other DNA damage/repair gene families, including histone variants H2a and H3a, which encode core histone proteins with substantial variations in their amino and C-terminal regions, DNA polymerase d (POLD) (32,33), and nucleotide excision repair-like (NEIL) (34,35), have been less well studied in CSR. Although AID is considered the master regulator of DNA breaks and NHEJ that enable CSR and we previously showed that a deficiency of IL-17RA in the lupus-prone BXD2 mice affected the expression of AID in vivo and diminished the development of IgG autoantibodies (12), how IL-23 or IL-17 regulate AID-induced NHEJ to promote CSR in immunized or spontaneously autoreactive GC B cells is largely unknown.…”
Section: Il-23 Promotes a Coordinated B Cell Germinal Center Program For Class-switch Recombination To Igg2b In Bxd2 Micementioning
confidence: 99%
“…Known classical NHEJ players include Ku70 (XRCC6), Ku80 (XRCC5), XRCC4, DNA ligase IV, and DNA-PKcs (29), whereas the nonclassical (or alternative) NHEJ pathway uses XRCC1 and DNA ligase III for DNA end joining (30,31). Other DNA damage/repair gene families, including histone variants H2a and H3a, which encode core histone proteins with substantial variations in their amino and C-terminal regions, DNA polymerase d (POLD) (32,33), and nucleotide excision repair-like (NEIL) (34,35), have been less well studied in CSR. Although AID is considered the master regulator of DNA breaks and NHEJ that enable CSR and we previously showed that a deficiency of IL-17RA in the lupus-prone BXD2 mice affected the expression of AID in vivo and diminished the development of IgG autoantibodies (12), how IL-23 or IL-17 regulate AID-induced NHEJ to promote CSR in immunized or spontaneously autoreactive GC B cells is largely unknown.…”
Section: Il-23 Promotes a Coordinated B Cell Germinal Center Program For Class-switch Recombination To Igg2b In Bxd2 Micementioning
confidence: 99%
“…Indeed, such differences may explain why Gh/Sp and FapyG lesions are processed more efficiently by Ed NEIL1. 28,57 The lesion-specific activity differences of UE versus Ed NEIL1 suggest that cellular responses to oxidative stress will be impacted by the relative amounts of the two isoforms. ADAR1 is induced in T-lymphocytes and macrophages by TNF-α and IFN-γ, 58−60 and therefore, Ed NEIL1 would likely be the predominant form present under conditions of inflammation.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Moreover, the relative impacts of NEIL1 recoding on lesion sensing, extrusion, and engagement versus enhancing lesion lability would be anticipated to be distinctly different due to the structural features of a given NEIL1 lesion substrate. Indeed, such differences may explain why Gh/Sp and FapyG lesions are processed more efficiently by Ed NEIL1. , …”
Section: Discussionmentioning
confidence: 99%
“…NEIL1 is a key human DNA glycosylase/AP lyase responsible for the removal of oxidatively induced lesions [reviewed in ref ]. Its substrates include 2,6-diamino-4-hydroxy-5-formamidopyrimidine (FapyGua), 4,6-diamino-5-formamidopyrimidine (FapyAde), thymine glycol (ThyGly), 5-hydroxycytosine (5-OH-Cyt), ,,, and the secondary oxidation products of 8-hydroxyguanine (8-OH-Gua), such as guanidinohydantoin (Gh) and diastereomers of spiroiminodihydantoin (Sp1 and Sp2). , ,, Consistent with this broad substrate specificity, NEIL1 also excises methyl- and nitrogen mustard-FapyGua adducts, , psoralen-induced DNA cross-links, , and other lesions. , There are two different forms of intracellular nuclear NEIL1 that arise from the processing of pre-mRNA by adenosine deaminase ADAR1, in which a single adenosine is converted to inosine. This deamination results in an amino acid change in NEIL1 of Lys242 to Arg242 (K242R) and is referred to as the edited form. ,,, Unless otherwise noted, throughout this investigation, we will use the edited form of the enzyme and refer to it as NEIL1.…”
Section: Introductionmentioning
confidence: 99%